SUSTAINABLE ECONOMICS IN THE DEVELOPMENT OF COUNTRIES - Bultakov , Sardor; Eshboyeva, Madina (Scientific practical conference, 2026)
Sustainable economic development has become an important priority for modern economies as countries face increasing environmental and social challenges. Traditional economic growth models often ignored ecological limits and social inequalities, which has resulted in environmental degradation and resource depletion. Sustainable economics provides an approach that integrates economic growth with environmental protection and social welfare. This article examines the role of sustainable economic principles in national development, focusing on efficient resource management, renewable energy transition, circular economy practices, and inclusive growth strategies. The study highlights the importance of sustainable policies in achieving long-term economic stability and environmental preservation.